Ultrasonic Speed and Related Acoustical Parameters of 1,1ʼ-Binaphthalene-2,2ʼ-diyl Diacetate Solutions at 308.15 K - Pooja P. Adroja; S. P. Gami; J. P. Patel; P. H. Parsania (E-Journal of Chemistry)
The density (ρ), viscosity (η) and ultrasonic speed (U) (2 MHz) of chloroform, THF, ethyl alcohol, ethyl acetate, 1,4-dioxane and 1,1ʼ-binaphthalene-2,2ʼ-diyl diacetate (DBNA) solutions have been determined at 308.15 K. Various acoustical parameters namely specific acoustical impedance (Z), adiabatic compressibility (κa), Van der Waals constant (b), intermolecular path length (Lf), internal pressure (π), Raoʼs molar sound function (R), relaxation time (τ), classical absorption coefficient (α/f2)cl and solvation number (Sn) have been derived from ρ, η and U data and correlated with concentration (C). A fairly good to excellent correlation has been observed between a particular parameter and C. Linear increase of Z, R, b, (α/f2)cl and τ (except EA) (R2 = 0.90 – 0.999) and linear decrease of κs, π and Lf (R2 = 0.947 – 0.995) with C supported existence of powerful molecular interactions in the solutions and further supported by nonlinear increase of Sn with C. A fairly constant Gibbs free energy of activation has been observed in all the solvent systems studied.